The relationship between esophageal peristalsis and in vivo intraband pressure measurements in gastric banding patients - Fried, Martin; Ghosh, Sudip K; Gutierrez, Mario; Dolezalova, Karin; Widenhouse, Tamara; Gayoso, Gaspar (Obesity surgery, 2010)
Intraband pressure (IBP) measurement may be a less invasive method to assess esophageal motility response to band adjustment and restrictive integrity of the device in Swedish adjustable gastric band (SAGB) patients. However, the relationship between IBP and esophageal function is not yet established. Our aim was to characterize in vivo IBP-peristalsis associations in SAGB patients. Ten patients in their second postoperative year were prospectively recruited. IBP was measured via percutaneous port, and concurrent esophageal manometry was performed using an 8-channel catheter. Contraction length and amplitude were measured with both methods. The IBP-peristalsis correlation was computed using the R-square of the regression analysis (R (2)) for band volumes ranging from 4 to 9 mL. One hundred ten swallows were studied. Excellent IBP-peristalsis correlation was observed in 6 of 10 patients (267 contractions): contraction length R (2) = 0.8537 and amplitude R (2) = 0.7365 (p-value of slope < 0.001). Mean contraction length was 17 +/- 7 (4-42) s for manometry and 18 +/- 7 (5-43) s for IBP. Mean amplitude was 55 +/- 55 (9-209) mm Hg for manometry and 67 +/- 47 (7-190) mm Hg for IBP. A weak IBP-peristalsis correlation was observed in the remaining four patients: two had impaired lower sphincter relaxation, one had band slippage, and one had disruption of the port needle connection. In vivo IBP measurement may be reliable in the assessment of esophageal peristalsis in response to band adjustments and the restrictive integrity of the device in patients with intact esophageal function. More studies are warranted to completely assess the potential for IBP to be indicative of the presence of band-related complications.
Keywords: poruchy motility jícnu; Manometry; Gastrointestinal Motility; morbidní obezita; Middle Aged; mužské pohlaví; gastroplastika; tlak; Pressure; Adult; Esophageal Motility Disorders; Esophageal Sphincter, Lower; Prospective Studies; polykání; Esophagus; Peristalsis; gastrointestinální motilita; manometrie; ženské pohlaví; dolní jícnový svěrač; peristaltika; Humans; prospektivní studie; Gastroplasty; lidé středního věku; dospělí; Female; ezofágus; Obesity, Morbid; lidé; Male; Deglutition